2013
DOI: 10.1063/1.4826078
|View full text |Cite
|
Sign up to set email alerts
|

Nanograting formation through surface plasmon fields induced by femtosecond laser pulses

Abstract: Ablation of solid surfaces irradiated with superimposed multiple shots of low fluence femtosecond (fs) laser pulses often results in the formation of periodic nanostructures on the target surface. We demonstrate that the self-organization process of nanostructuring can be regulated to fabricate a homogeneous nanograting on the target surface in air. A simple two-step ablation process was used to control the nanoscale energy deposition that should be developed through the excitation of surface plasmon polariton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…9,10 Under this condition, we have shown that a flat target surface is nanostructured through bonding structure change of the material, [11][12][13] near-field ablation around the corrugated nanosurface, [13][14][15] and excitation of standing surface plasmon polariton (SPP) waves. [15][16][17] These interaction processes could explain the origin and growth of PNSs on DLC, 15 Si, 16 and GaN, 17 where the theoretical calculation reproduced well the observed nanoperiod much smaller than $k/2. Based on the mechanism, we developed a two-step ablation technique to control the interaction and imprint a homogeneous nanograting in air.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…9,10 Under this condition, we have shown that a flat target surface is nanostructured through bonding structure change of the material, [11][12][13] near-field ablation around the corrugated nanosurface, [13][14][15] and excitation of standing surface plasmon polariton (SPP) waves. [15][16][17] These interaction processes could explain the origin and growth of PNSs on DLC, 15 Si, 16 and GaN, 17 where the theoretical calculation reproduced well the observed nanoperiod much smaller than $k/2. Based on the mechanism, we developed a two-step ablation technique to control the interaction and imprint a homogeneous nanograting in air.…”
mentioning
confidence: 70%
“…Based on the mechanism, we developed a two-step ablation technique to control the interaction and imprint a homogeneous nanograting in air. 17 In contrast, only a few kinds of metals are known of which surfaces have been periodically nanostructured through the fs-laser ablation in air. Stainless steel (SUS) [18][19][20] and Ti 7,21-24 are the most common metals structured at the groove period smaller than $k/2, while the PNS formation was observed for Cu, 25,26 Al, 27 and W 28 under the specific conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SPP wave between dielectric (glass) and plasma can be launched when Re( ε p ) ≤ − n 2 , where ε p is the permittivity of plasma at the focal volume (a necessary condition with the Bragg phase-matching being the satisfactory condition)1131323334. This follows from the requirement of the wave vector of the surface wave to be a real number, where k 0  = 2 π / λ .…”
Section: Resultsmentioning
confidence: 99%
“…Periodic nanostructures can be created with femtosecond lasers on metals [6][7][8][9][10], semiconductors [11][12][13][14][15][16][17][18][19] and also inside transparent materials [20]. The periodic nanostructures are self-organized in the laserfocused spot, and their arrangement depends on the laser wavelength.…”
Section: Introductionmentioning
confidence: 99%